Dynamic contrast-enhanced magnetic resonance imaging identifies a subgroup of patients with asymptomatic monoclonal plasma cell disease and pathologic microcirculation - Hillengaß, Jens; Zechmann, Christian; Bäuerle, Tobias; Wagner-Gund, Barbara; Heiß, Christiane; Benner, Axel; Ho, Anthony Dick; Neben, Kai; Hose, Dirk; Kauczor, Hans-Ulrich; Goldschmidt, Hartmut; Delorme, Stefan; et al. (Clinical cancer research, 2009)
PURPOSE: The aim of our study was to investigate whether dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) allows visualization of changes in microcirculation between healthy controls on the one side and early/advanced stages of plasma cell disease on the other. - EXPERIMENTAL DESIGN: We examined a group of 222 individuals consisting of 60 patients with monoclonal gammopathy of undetermined significance (MGUS), 65 patients with asymptomatic multiple myeloma (aMM), 75 patients with newly diagnosed symptomatic MM (sMM), and 22 healthy controls with DCE-MRI of the lumbar spine. - RESULTS: A continuous increase in microcirculation parameters amplitude A and exchange rate constant kep reflecting vascular volume and permeability, respectively, was detected from normal controls over MGUS and aMM to sMM. For A and kep, significant differences were found between controls and aMM (P = 0.03 and P = 0.004, respectively) as well as controls and sMM (P = 0.001 and P < 0.001, respectively). Although diffuse microcirculation patterns were found in healthy controls as well as MGUS and MM, a pattern with focal hotspots was exclusively detected in 42.6% of sMM and in 3 MGUS and 3 aMM patients. MGUS and aMM patients with increased microcirculation patterns showed significantly higher bone marrow plasmocytosis compared with patients with a low microcirculation pattern. - CONCLUSIONS: Our investigations substantiate the concept of an angiogenic switch from early plasma cell disorders to sMM. Pathologic DCE-MRI findings correlate with adverse prognostic factors and DCE-MRI identifies a distinct group of patients with increased microcirculation parameters in aMM and MGUS patients.
Gesehen am 14.01.2022